(untitled) - Wolff, Hans Walter; (1911-1993) (U.S.A, 1990)
Wolff's commentary on Micah is one of the most thorough works available in English. His insightful observations on the message of the prophet make this book a standard commentary on Micah for years to come. It is highly recommended to scholars, ministers, and theological students as an indispensable aid.
Keywords: Bible -- Micah -- Commentaries